Joint Sub-Channel Assignment and Power Allocation in Heterogeneous Networks: An Efficient Optimization Method - Khamidehi, Behzad; Rahmati, Ali; Sabbaghian, Maryam (IEEE communications letters, 2016)
This letter is concerned with joint sub-channel and power allocation in a heterogeneous network. We consider the uplink of a co-channel framework where a macrocell shares the orthogonal frequency division multiple access (OFDMA) sub-channels with a number of small cells (SCs). We maximize the weighted sum-rate of the OFDMA SC network, while a target constraint on the cross-tier interference and a minimum data rate requirement for the high data rate SC users are satisfied. The optimization problem is a highly non-convex mixed integer non-linear problem. We first reformulate the problem into a more mathematically tractable form. Then, we relax the integer variables by adding a penalty term to the objective function. Finally, we rewrite the objective function as the difference of two concave (D.C.) functions and solve this problem using the successive convex approximation method. We show that our method outperforms the state-of-the-art schemes.